CASE STUDY OF CONDUCT IMITATES LIFE STYLE KOREA IN ADOLESCENT - Sander, Alex (EMPATHY Jurnal Fakultas Psikologi, 2013)
Abstract The strategy used in this study is a case study, as a case study approach allowed the researchers to gain an understanding of the interrelated whole and integrated range of facts and dimensions of the cases studied. The purpose of this research is to determine how the image of Korean life imitating behavior in adolescents. Factors that influence adolescents imitate Korean lifestyle and psychosocial effects mimic Korean lifestyle in adolescents. In this study, determination of sampling in accordance with specific criteria that have been determined (criterion sampling). The research took two people from the respondents were older high school graduates go to college in Yogyakarta. Data Collection Methods in this study in the form of observation, semi-structured interviews and document study. The results of this study found that, mimicking the behavior of Korean lifestyle on the subject I is influenced by external factors such as positive reinforcement from the media, and the conditioning of the surrounding environment. While on the subject II is influenced by external factors such as positive reinforcement from the media, friends and conditioning of the surrounding environment. The impact of life imitating Korea. Namely, on the subject I, feel satisfied, his confidence increased, bigotry against idol, a addiet media (TV, CDs, magazines). While on the subject II, his confidence increased, a personal individualistic society like Korea, Consumptive against Korean entertainment, and want to figure idoanya. Conclusions in this study mimic the behavior of Korean lifestyle is found that both subjects using a different form in imitation. On the subject of I, he used a form of imitation modeling. While on the subject II using impersonation form of identification. Kata kunci : Observation learning, Imitation learning, Identifikation.